The Effect of Educational Exercises and Added Weights in Some Kinematic Variations of the Performance Angle of the Shudder Effect on the Horizontal Bar of Youngsters - Nada Ibrahim Abdulreda (Journal of Global Pharma Technology, 2019)
The objective of the research was to prepare educational exercises and weights to improve and develop some kinetic variables for the performance angles of the skill of the generator on the young Horizontal bar machine and also to identify the kinetic variables for the performance angles of the skill either hypothesized. The research and training program had a positive effect on some kinetic variables for performance angles of the skill of the catalyst, Statistical significance between the results of the tribes and Posttests of the research sample in some kinetic parameters of the performance angles of the skill of the generator on the brain of young people. The researcher used the experimental method in designing a single group as well as the use of video imaging and determined the research community in a deliberate manner. The pilot experiment was conducted. The experiment was carried out by a group of six players, aged 10-13 years. And then the tests of the Pre group of research and then were applied educational exercises and exercises with weights added two (14) week and the existence of three training units per week and the number of educational units and training (42) training unit and when the program was completed tests dimensionality and processing the results statistically. The fourth part included presentation, analysis and discussion of the results. The researchers concluded that the educational exercises and the added weights contribute to the improvement of some kinematic variety of the performance angles of the skill of the skeletal system in the brain of young people and recommended the use of educational exercises and exercises in weights added to other skills in the gymnastic and other devices. The trainers should take into account the values of the biochemistry variables that have been achieved when training the performance angles of the skill of the generator on the brain of young people.Keywords: Educational Exercises, Weights Kinematic Variations, Performance Angle, Shudder Effect and the Horizontal bar.